1994
DOI: 10.1123/ijsn.4.2.175
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Consequences of Subclinical Eating Disorders in Female Athletes

Abstract: A growing body of evidence suggests that the prevalence of eating disorders and excessive concerns regarding body weight in certain subpopulations of female athletes are increasing. The pressure on female athletes to improve their performances and physiques, coupled with the general sociocultural demand placed on all women to be thin, often results in attempts to achieve unrealistic body size and body weight goals. For some female athletes the pressure to achieve and maintain a low body weight leads to potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 88 publications
2
66
0
2
Order By: Relevance
“…[1][2][3] Determining the exact prevalence of eating disorders and disordered eating behaviors is difficult because those affected may not report the behavior or not seek treatment, thus making occurrence estimates somewhat unreliable. 4 Researchers [5][6][7][8][9] have been studying the nature and scope of eating-related problems among female athletes for many years, and identifying at-risk athletes remains a challenge. Interestingly, results are mixed as to which female athletes are more susceptible to eating disorders and disordered eating behaviors and whether athletes are at a higher risk compared with females in the general population.…”
mentioning
confidence: 99%
“…[1][2][3] Determining the exact prevalence of eating disorders and disordered eating behaviors is difficult because those affected may not report the behavior or not seek treatment, thus making occurrence estimates somewhat unreliable. 4 Researchers [5][6][7][8][9] have been studying the nature and scope of eating-related problems among female athletes for many years, and identifying at-risk athletes remains a challenge. Interestingly, results are mixed as to which female athletes are more susceptible to eating disorders and disordered eating behaviors and whether athletes are at a higher risk compared with females in the general population.…”
mentioning
confidence: 99%
“…One of the following symptoms must also be present: delayed puberty, menstrual dysfunction, disturbance in body image, use of purging methods, binge eating, or compulsive exercising. Beals and Manore [9] presented similar criteria, except that distorted body image and limiting food choices or food groups were in the criteria absolutely necessary for diagnosis, and gastrointestinal complaints were in the relative criteria, only one of which is required for diagnosis. Beals and Manore suggested that further research was needed to determine what number of symptoms should be required to meet the criteria for AA.…”
Section: Diagnosismentioning
confidence: 99%
“…There is literature on "anorexia athletica" (AA) that removes the criterion of the 85% cutoff, and therefore it might be considered an EDNOS. Although AA may be a subclinical eating disorder, it can still lead to medical and mental health complications [9]. Sundgot-Borgen [3] set criteria for AA that must involve weight loss, gastrointestinal complaints, the absence of medical or affective disorder explaining the weight loss, excessive fear of becoming obese, and restriction of caloric intake.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In these instances, individuals may have some eating and body-weight problems but fail to meet all of the DSM criteria for anorexia, bulimia, or EDNOS (Beals & Manore, 1994). These symptoms may include behaviors such as restricting food intake or bingeing on food, excessive exercise, occasionally purging, or the use of laxatives or weight loss pills.…”
Section: Definitionmentioning
confidence: 99%